100 taon 100 Filipina sa digmaan at sa kapayapaan - Camacho, Leonarda Navato ([Quezon City s.n.] e(Diliman, Quezon City fSBA Printers), 2000)
Brief biography of Filipina prominent women.
In Tagalog.
Keywords: Women -- Philippines -- Biography